Psocoptera captured by using a suction trap in Valtellina during 1992-1993 (Bollettino di zoologia agraria e bachicoltura, 2024)
During 1992-1993, in the province of Sondrio (Ponte in Valtellina), by using a Taylor suction trap, 14 species of Psocoptera were collected and identified, in particular Elipsocus hyalinus (Stephens) and Lachesilla greeni Pearman were recorded for the first time in Italy. In both years the first catches occurred in May, the last ones at the beginning of November. The highest number of catches was recorded from the end of July to the end of September.
Keywords: Psocoptera; new records; Italy